2014
DOI: 10.1111/jan.12551
|View full text |Cite
|
Sign up to set email alerts
|

Narratives of family transition during the first year post‐head injury: perspectives of the non‐injured members

Abstract: Aim. To explore the narratives created by non-injured family members in relation to themselves and their family in the first year after head injury. Background.A head injury is a potentially devastating injury. The family responds to this injury by supporting the individual and their recovery. While the perspective of individual family members has been well documented, there is growing interest in how the family as a whole makes sense of their experiences and how these experiences change over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…This paper reports data from a larger study that investigated the effect of TBI on the uninjured members of a family in the first year following injury. The full findings of this study are reported elsewhere (see Whiffin, 2012) and an exploration of how family members talked about the impact of TBI on themselves and their family was discussed in Whiffin et al (2015). However, the aim of this paper is to describe the narrative structures used by the uninjured members of a family to understand change.…”
Section: Aimmentioning
confidence: 89%
See 1 more Smart Citation
“…This paper reports data from a larger study that investigated the effect of TBI on the uninjured members of a family in the first year following injury. The full findings of this study are reported elsewhere (see Whiffin, 2012) and an exploration of how family members talked about the impact of TBI on themselves and their family was discussed in Whiffin et al (2015). However, the aim of this paper is to describe the narrative structures used by the uninjured members of a family to understand change.…”
Section: Aimmentioning
confidence: 89%
“…Ownsworth and Haslam (2016) have highlighted that, 'It is well recognised that brain injury can lead to significant loss and change in social relationships, and it is only when we understand how central they are to self-definition, that we can start to understand why such loss affects people so deeply' (p26). It has been argued that understanding the family context can help us to understand further how families adjust, cope and adapt post-TBI (Jumisko, Lexell, & Soderberg, 2007;Whiffin, Bailey, Ellis-Hill, Jarrett, & Hutchinson, 2015;Yeates, Henwood, Gracey, & Evans, 2007).…”
Section: Family Context In Tbimentioning
confidence: 99%
“…It is essential to understand the experiences and perceptions of patients and carers during the transitional phase to inform improvements to service delivery to meet their needs [10]. Although there is some relevant literature [9,10,[32][33][34][35] studies often conflate mild, moderate and severe TBI [6,17,[35][36][37], use a sample with mixed brain injury diagnoses [11,17], adhere to quantitative measures [16,36,37] or do 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 not focus solely on the transition period [6,15,16,36]. Thus there appears to be a gap in understanding what is important and beneficial to patients with severe TBI, and their and carers, in the context of UK healthcare in this transitional phase, and how best to meet these needs.…”
Section: Current Practicementioning
confidence: 99%
“…A narrative case study was designed to explore the personal and family changes reported by noninjured family members at three time points during the first year of a family member's traumatic brain injury (Whiffin 2012). Three families were considered individual cases and each case comprised a number of family members, each of whom completed in-depth interviews at one, three and twelve months post-injury.…”
Section: The Studymentioning
confidence: 99%